Complications of plate fixation of femoral shaft fractures in children and adolescents. (June 2013) - May, Collin; Yen, Yi-Meng; Nasreddine, Adam Y.; Hedequist, Daniel; Hresko, Michael T.; Heyworth, Benton E.
Abstract: Purpose: This study aims to critically analyze the major and minor complications that may be associated with plate fixation of pediatric diaphyseal femur fractures. Methods: The medical records of skeletally immature patients (6–15 years of age) who underwent plate fixation of a diaphyseal femur fracture at a tertiary-care level-1 pediatric trauma center between 1/2003 and 12/2010 were reviewed. Demographic and clinical information regarding the mechanism of injury, fracture type, and surgical technique were recorded. Radiographic evaluation of bony healing, hardware position, and deformity was performed throughout the study period. All intraoperative and postoperative complications were recorded. Complication incidence and time from surgery to complication were described. Multivariate logistic regression and multivariate Cox regression models were used to assess the association between different variables and the occurrence of a complication. Kaplan–Meier survivorship curves were used to evaluate the freedom from a complication with longer follow-up. Results: Over an 8-year period, 85 skeletally immature patients (83 % males, mean age 10.2 years) underwent plate fixation for diaphyseal femur fractures. Overall, complications were identified in 11 patients (13 %). Major complications, defined as those resulting in unplanned reoperation (excluding elective removal of asymptomatic plate/screws), occurred in five patients (6 %) and included two patients (2 %) with wound infections requiring irrigation and debridement, two patients (2 %) with distal femoral valgus deformity (DFVD) leading to osteotomy and hardware removal, respectively, and one patient (1 %) with a 3-cm leg length discrepancy (LLD) requiring epiphysiodesis. Minor complications, defined as those not requiring unplanned operative intervention, occurred in six patients (7 %) and included two patients (2 %) with delayed union, two patients (2 %) with symptomatic screw prominence, one patient (1 %) with a superficial wound infection effectively treated with oral antibiotics, and one patient (1 %) with valgus malunion, which was asymptomatic at early follow-up. There were no intraoperative complications and no reports of postoperative knee stiffness, shortening, or reoperations to address fracture stability. Fifty-two patients (61 %) underwent routine elective removal of hardware without related complications following fracture union. Overall, complications occurred postoperatively at a mean time of 20 months (range 0–65 months), though major complications occurred at a later time point (mean 29.1 months, range 0–65 months) than minor complications (mean 12.5 months, range 0–40.1 months). Longer follow-up was associated with higher occurrence of a complication [ p = 0.0012, odds ratio = 1.05, 95 % confidence interval (CI): 1.02–1.08]. Conclusions: The plating of pediatric femur fractures is associated with 6 and 7 % rates of major and minor complications, respectively. There were minimal long-term sequelae associated with the complications noted. This complication rate compares favorably with the published rate of complications (10–62 %) associated with titanium elastic nail fixation of similar fracture types. Most complications occurred >4 months postoperatively, with major complications occurring at a later time point than minor complications. Long-term follow-up of these patients is recommended to ensure that complications do not go undetected. Level of evidence: Retrospective case series, Level IV.